Limitações humanas do operador de máquinas agrícolas e o ambiente socio-laboral na sojicultura - Silva, Rogério de Abreu [UNESP] (2014)
Soybean [Glycine max (L.) Merrill] is a very important product in the Brazilian agribusiness and has gained a prominent position in the agricultural scenario of the state of Maranhão. Soybean culture system requires an intense agricultural mechanization process which influences, and is influenced by, the social and work environment of the agricultural machine-operator. This is a case study of agricultural machine-operators engaged in the process of soybean planting mechanization that took place in the municipality of Balsas, south Maranhão. The objective of the present study was to assess the potential influences of the operator's socio-labor environment on their own limitations. Data were obtained via direct observations and self-report questionnaires. It is concluded that the current agricultural work relationships requires a new profile of rural workers, in which minimal effects on the operator's environmental limitations and significant effects on the technical, physical, physiological and psychological limitations of these workers as well as on the agricultural mechanization process should be generated by the socio-labor environment. Skill training courses should be offered to the rural workers in order to support and help them to supplant their limitations